Characteristics, Management, and Prognosis of Spontaneous Coronary Intramural Hematoma. (April 2022) - Chang, Shufu; Dai, Yuxiang; Song, Xiaoyue; Li, Chenguang; Lu, Hao; Huang, Zheyong; Ma, Jianying; Qian, Juying; Ge, Junbo
Spontaneous coronary intramural hematoma (SCIH) was one type of spontaneous coronary artery dissection without obvious intimal tear, which is easy to misdiagnose. We aimed to study the characteristics, management, and prognosis of SCIH in our center. All the SCIH patients (n = 30) diagnosed by coronary angiography from January 1, 2012 to December 31, 2018 were enrolled. The demographic characteristics, history, therapy, and follow-up were collected. The mean age of the patients was 51.8 ± 9.5 years. Most of the patients were females (66.7%) with hypertension. Patients with diffuse lesion, focal lesion, and multiple vessels were 70%, 13.3%, and 16.7%, respectively. Conservative treatment was the first choice (76.7%). The mean follow-up time was 29.3 ± 13.5 months. None of the patients had unplanned readmission due to worsening symptoms. Nine patients underwent coronary artery computed tomography reexamination after 10.3 ± 7.5 months, which showed complete recovery of SCIH. Eight patients were hospitalized for coronary angiography 6.4 ± 4.7 months later, which did not show any sign of SCIH. Spontaneous coronary intramural hematoma was most common in post-menopausal women with hypertension. Possibly, antiplatelet drugs should be avoided in SCIH. Waiting for the hematoma to heal was preferable and had a good prognosis.